THE IMPORTANCE OF TEACHING CULTURE IN EFL CLASSROOMS: THE IMPORTANCE OF TEACHING CULTURE IN EFL CLASSROOMS - Atamuratova, Jadira (Журнал иностранных языков и лингвистики, 2025)
The growing awareness of the intertwined nature of culture-language has led to academic studies and articles encouraging educators to place significantly more emphasis on teaching about the target culture. Authors, such as Byram (1989), H. D. Brown (2007), Peck (1998), Atkinson (1999), Moran (2001), and Mishan (2005) have discussed culture as an important and necessary component in an effective language curriculum. In this context, Byram has written that his main goal is to develop “an integrated discipline of teaching language and culture” [1; 23]. Moran subsequently added that cultural awareness helps students discover and explore their personal perspectives, not only on the target culture but the world as a whole [5; 75]. Whatever the motivation and reasons, learning a foreign language is always “culture- bounded” [8; 112]. The flip side of the coin is that the features of a target culture cannot be deeply taught without integrating instruction in the target culture’s language.